Incidence and predictors of surgical site infections following caesarean sections at Bugando Medical Centre, Mwanza, Tanzania - Mpogoro, Filbert J (BioMed Central, 2014)
BACKGROUND: Surgical site infection (SSI) is the second most common infectious complication after urinary tract infection following a delivery by caesarean section (CS). At Bugando Medical Centre there has no study documenting the epidemiology of SSI after CS despite the large number of CSs performed and the relatively common occurrence of SSIs. METHODS: This was a prospective cohort study involving pregnant women who underwent a CS between October 2011 and February 2012 at Bugando Medical Centre. A total of 345 pregnant women were enrolled. Preoperative, intraoperative and postoperative data were collected using a standardized questionnaire. Wound specimens were collected and processed as per standard operative procedures; and susceptibility testing was carried out using a disc diffusion technique. Data was analyzed using STATA version 11. RESULTS: The overall cumulative incidence of SSI was 10.9% with an incidence rate of 37.5 per 10,000 people/day (95% CI, 26.8-52.4). The median time from CS to the development of SSI was 7 days (interquartile range [IQR] = 6–9 days). Six independent risk factors for post caesarean SSI as identified in this study by multivariate analysis are: hypertensive disorders of pregnancy (HR: 2.5; 95% CI, 1.1-5.6; P = 0.021), severe anaemia (HR: 3.8; 95% CI, 1.2-12.4, P = 0.028), surgical wound class III (HR: 2.4; 95% CI, 1.1-5.0; P = 0.021), multiple vaginal examinations (HR: 2.5; 95% CI, 1.2-5.1; P = 0.011), prolonged duration of operation (HR: 2.6; 95% CI, 1.2-5.5; P = 0.015) and an operation performed by an intern or junior doctor (HR: 4.0; 95% CI, 1.7-9.2; P = 0.001). Staphylococcus aureus was the most common organism (27.3%), followed by Klebsiella pneumoniae (22.7%). Patients with a SSI had a longer average hospital stay than those without a SSI (12.7 ± 6.9 vs. 4 ± 1.7; P < 0.0001) and the case fatality rate among patients with a SSI was 2.9%. CONCLUSION: SSIs are common among women undergoing CSs at Bugando Medical Centre. SSIs were commonly associated with multiple factors. Strategies to control these factors are urgently needed to control SSIs post CS at Bugando Medical Centre and other centres in developing countries.